Hillbilly Hustle - Browne, Wesley, 1974- (Book collections on Project MUSE., 2020)
"Knox Thompson thinks he's working a hustle, but it's a hustle that's working him. Trying to keep his pizza shop and parents afloat, he cleans out a backroom Kentucky poker game, only to get roped into dealing marijuana by the proprietor-an arrangement Knox only halfheartedly resists"--